Are the Sustainable Development Goals really sustainable? A policy perspective. (13th August 2020) - Jain, Prerna; Jain, Pragati
Abstract: Sustainable development seeks human well‐being without stretching the ecological limits. It is assumed that if sustainable development is aspired at global level, the goals prescribed should be within the planetary limits. A comparison of the scores of countries with respect to Sustainable Development Goal Index (SDGI) and scores on Ecological Footprints (EF) portrays quite a grim picture where countries with high EF have attained high scores on SDGI. A further investigation into the causal relationship between SDGI, Human Development Index (HDI) and EF reveals that SDGs are being achieved in an unsustainable manner. The environmental policy perspective of the total, direct and indirect effects of EF on SDGs estimated through path analysis unveils that the existing mode of achieving SDGs is at the cost of environmental degradation. SDGs have shown improvement through the improvement in the level of HDI, where human development is being attained in an environmentally unsustainable manner. The paper establishes that SDGs achieved are ecologically unjustifiable, and a reorientation of the existing patterns of human development well within the limits of ecological capacity of the earth is to be targeted.